2016
DOI: 10.1017/gmh.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Local perceptions of the impact of group interpersonal psychotherapy in rural Uganda

Abstract: Background.This study investigated local perceptions of changes stemming from a long-standing Group Interpersonal Psychotherapy (IPT-G) program for the treatment of depression in rural Uganda. The study was conducted in a low-income, severely HIV/AIDS-affected area where in 2001 the prevalence of depression was estimated at 21% among adults.Method.Data were collected using free-listing and key informant qualitative interviews. A convenience sample of 60 free-list respondents was selected from among IPT-G parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In comparison to a similar intervention (Petersen et al 2014), the low rate of attrition in our study provides evidence of IPT-G as a feasible and effective PT for moderate-to-severe depression when delivered by trained LCHWs within a task-shifting approach in low-resource settings. Though there are concerns about fidelity and other barriers to effective IPT-G delivery (Lewandowski et al 2016), integration within government health system structures may provide the right platform for sustainable service provision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to a similar intervention (Petersen et al 2014), the low rate of attrition in our study provides evidence of IPT-G as a feasible and effective PT for moderate-to-severe depression when delivered by trained LCHWs within a task-shifting approach in low-resource settings. Though there are concerns about fidelity and other barriers to effective IPT-G delivery (Lewandowski et al 2016), integration within government health system structures may provide the right platform for sustainable service provision.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates that an evidence-based psychotherapy intervention can be delivered effectively and with fidelity by lay counsellors and, critically, that the effects of the intervention on the primary depression outcome were sustained over a 6-month period following the end of the treatment. Lewandowski & others (2016) provide more evidence of sustained effects of IPT-G: positive changes in quality of life and a range of non-mental health outcomes were attributed to the treatment 10 years after the intervention (Lewandowski et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A long-term follow up of group-based interpersonal psychotherapy (IPT) found that the groups continued to meet several years later (Lewandowski et al, 2016), so this finding of continued group meetings may be an important factor to explore in future group-based treatment studies. We did not find participant-level characteristics (demographics, recent trauma history, initial baseline scores) that differentiated which women were able to maintain the treatment impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health programming in humanitarian settings can impact community well‐being beyond symptom reduction, as participants in similar group interventions have reported increased family cohesion and reduced familial conflict (Lewandowski et al., 2016). However, the extent to which these and positive findings for mental health symptoms can be sustained despite a lack of sustained organizational support is uncertain.…”
mentioning
confidence: 99%